Early Aortic Valve Replacement vs. Conservative Management in Asymptomatic Severe Aortic Stenosis Patients With Preserved Ejection Fraction: A Meta-Analysis - Yuan, Tan; Lu, Yi; Bian, Chang; Cai, Zhejun (Frontiers in Cardiovascular Medicine, 2021)
Background: Aortic stenosis (AS) is the most common valvular disease in developed countries. Until now, the specific timing of intervention for asymptomatic patients with severe aortic stenosis and preserved ejection fraction remains controversial. Methods: A systematic search of four databases (Pubmed, Web of science, Cochrane library, Embase) was conducted. Studies of asymptomatic patients with severe AS or very severe AS and preserved left ventricular ejection fraction underwent early aortic valve replacement (AVR) or conservative care were included. The end points included all-cause mortality, cardiac mortality, and non-cardiac mortality. Results: Four eligible studies were identified with a total of 1,249 participants. Compared to conservative management, patients who underwent early AVR were associated with lower all-cause mortality, cardiac mortality, and non-cardiac mortality rate (OR 0.16, 95% CI 0.09–0.31, P < 0.00001; OR 0.12, 95% CI 0.02–0.62, P = 0.01; OR 0.36, 95% CI 0.21–0.63, P = 0.0003, respectively). Conclusions: Early AVR is preferable for asymptomatic severe AS patients with preserved ejection fraction.